Investigating the Association Between the Caecal Microbiomes of Broilers and Campylobacter Burden - Sakaridis, Ioannis; Ellis, Richard J.; Cawthraw, Shaun A.; van Vliet, Arnoud H. M.; Stekel, Dov J.; Penell, Johanna; Chambers, Mark; La Ragione, Roberto M.; Cook, Alasdair J. (Frontiers in Microbiology, 2018)
One of the major transmission routes for the foodborne bacterial pathogen Campylobacter is undercooked poultry meat, contaminated from intestinal contents during processing. In broilers, Campylobacter can grow to very high densities in the caeca, and is often considered to be a commensal or an opportunistic pathogen in poultry. Reduction of caecal loads of Campylobacter may assist in lowering incidence rates of Campylobacter food poisoning. To achieve this, there needs to be a better understanding of the dynamics of Campylobacter colonisation in its natural niche, and the effect of the local microbiome on colonisation. Previous studies have shown that the microbiome differed between Campylobacter colonised and non–colonised chicken intestinal samples. To characterise the microbiome of Campylobacter-colonised broilers, caecal samples of 100 randomly selected birds from four farms were analysed using amplified 16S rRNA gene sequences. Bacterial taxonomic analysis indicated that inter-farm variation was greater than intra-farm variation. The two most common bacterial groups were Bacteroidetes and Firmicutes which were present in all samples and constituted 29.7 – 63.5% and 30.2 – 59.8% of the bacteria present, respectively. Campylobacter was cultured from all samples, ranging from 2 to 9 log10 CFU g-1. There was no clear link between Campylobacter counts and Firmicutes, Bacteroidetes or Tenericutes levels in the 16S rRNA Operational Taxonomic Unit (OTU)-based analysis of the caecal microbiome, but samples with high Campylobacter counts (> 9 log CFU g-1) contained increased levels of Enterobacteriaceae. A decrease in Lactobacillus abundance in chicken caeca was also associated with high Campylobacter loads. The reported associations with Lactobacillus and Enterobacteriaceae match changes in the intestinal microbiome of chickens and mice previously reported for Campylobacter infection, and raises the question about temporality and causation; as to whether increases in Campylobacter loads create conditions adverse to Lactobacilli and/or beneficial to Enterobacteriaceae, or that changes in Lactobacilli and Enterobacteriaceae levels created conditions beneficial for Campylobacter colonisation. If these changes can be controlled, this may open opportunities for modulation of chicken microbiota to reduce Campylobacter levels for improved food safety.